Three-Dimensional Analysis Comparing Changes in Soft Tissue with Those in Hard Tissue following Orthognathic Surgery in Patients Showing Mandibular Prognathism with Facial Asymmetry - TERADA, KAZUTO; SAITO, CHIKARA; NAKAMURA, JUNICHI; NAKAGAWA, KOKI; MATSUBARA, TAIKI; TAKAKI, RITSUO; KAWAHARA, NOZOMI; MORITA, SHUICHI; HAYASHI, TAKAFUMI; YAMAZAKI, KOICHI; SAITO, ISAO (The Japanese Journal of Jaw Deformities, 2005)
The purpose of this study was to compare changes in soft tissue with those in hard tissue following orthognathic surgery in patients showing mandibular prognathism with facial asymmetry and to clarify the rate of soft tissue change to hard tissue change using reconstructed 3D-CT images. The subjects comprised four patients diagnosed as mandibular prognathism with facial asymmetry and treated byorthognathic two-jaw surgery. Pre- and posttreatment CT images were taken as data for precise diagnosis in all subjects. After reconstruction of 3D-CT images with the 3D reconstruction software Volume Extractor, four reconstructed 3D-CT images of both hard and soft tissues for pre- and post-treatment were exported to the 3D measurement software 3D-Rugle, and then those three-dimension coordinate systems were unified. First, the thickness of preoperative soft tissue and theamount of changes in hard tissue and soft tissue following orthognathic surgery were measured by 3D-Rugle. Then, in order to clarify the rate of soft tissue change to hard tissue change, linear regression analysis was performed and the regression parameter (amount of soft tissue change/amount of hard tissue change) was examined. Results were as follows: The rate of soft tissue change to hard tissue change in retrusion points showed a higher value in mentum than in the buccal region, and a higher value on the deviation side than on the non-deviationside. On the other hand, the rate of soft tissue change to hard tissue change displayed a lower value in protrusion points than that in retrusion points both on the deviation side and non-deviation side in the buccal region.Moreover, the coefficient of determination for protrusion change exhibited a smaller value than that for retrusion change.These facts suggest that it is more difficult to predictprotrusion change than retrusion change. Although the conventional cephalograms were unabled to precisely evaluate the difference between the right and left regions in patients with facial asymmetry, the three-dimensional analysis performed in this study was excellent in the detectability of difference between the right and left regions.Further, the present method enabled us to analyze widely and objectively the amount of soft tissue change to the amount of hard-tissue change following orthognathic surgery.Therefore, the rate of soft tissue change to hard tissue change obtained in this study is possibly useful in developing a system for predicting soft tissue change accompanied by orthognathic surgery.